1994
DOI: 10.1113/expphysiol.1994.sp003788
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of milk fat on milk secretion in the mouse: a re‐examination

Abstract: SUMMARYLactating mice were treated i.P. with cow milk, skim milk, milk lipid extract, preparations of milk fat globule membranes and fat globule-enriched milk (cream). Milk, but not skim milk, inhibited litter growth significantly. None of the fractions of milk fat globules had any apparent effect on litter growth. Litter growth was reduced markedly and maternal health adversely affected by cream. It is concluded that previous studies in which milk was injected I.P. cannot be taken to indicate that milk contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Heesom et al (1992) suggested that FIL may regulate lactose and casein synthesis, whereas fat synthesis may be regulated by a negative feedback mechanism involving medium chain fatty acids. To test this hypothesis, Peaker and Taylor (1994) investigated the effect of milk fat on litter weight gain in mice. Intraperitoneal injection of whole milk (which contains milk fat globules) into lactating mice inhibited litter growth, whereas skim milk (which was supposed to contain FIL) or fractions of milk fat globules alone had no effect.…”
Section: Local Regulation Of Milk Production and Mammary Functionmentioning
confidence: 99%
“…Heesom et al (1992) suggested that FIL may regulate lactose and casein synthesis, whereas fat synthesis may be regulated by a negative feedback mechanism involving medium chain fatty acids. To test this hypothesis, Peaker and Taylor (1994) investigated the effect of milk fat on litter weight gain in mice. Intraperitoneal injection of whole milk (which contains milk fat globules) into lactating mice inhibited litter growth, whereas skim milk (which was supposed to contain FIL) or fractions of milk fat globules alone had no effect.…”
Section: Local Regulation Of Milk Production and Mammary Functionmentioning
confidence: 99%
“…Heesom et al (1992) suggested that FIL may regulate lactose and casein synthesis, whereas fat synthesis may be regulated by a negative feedback mechanism involving medium chain fatty acids. To test this hypothesis, Peaker and Taylor (1994) investigated the effect of milk fat on litter weight gain in mice. Infusion of whole milk (which contains milk fat globules) into the mammary glands of lactating mice inhibited litter growth, whereas skim milk (which contains FIL) or fractions of milk fat globules alone had no effect.…”
Section: Negative Feedback On Milk Fat Synthesismentioning
confidence: 99%